2006
DOI: 10.1055/s-2005-873181
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine Oxidase Inhibitors from the Flowers ofChrysanthemum sinense

Abstract: From the MeOH extract of the flowers of Chrysanthemum sinense, a new flavone glucoside, acacetin 7- O-(3- O-acetyl- beta- D-glucopyranoside), has been isolated together with 27 known compounds including flavonoids, caffeoylquinic acid derivatives, phenolics, and a monoterpenoid glucoside. Their structures were elucidated on the basis of spectroscopic data. Compounds and displayed significant xanthine oxidase inhibitory activity in a concentration-dependent manner, and compounds and showed more potent inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
65
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 15 publications
7
65
0
1
Order By: Relevance
“…9) Our results suggested that flavonoids and caffeoylquinic acid derivatives are the active XO inhibitory constituents in the flowers of C. sinense. Flavonoids and caffeoylquinic acid derivatives are groups of natural products with varied biological and pharmacological activities.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…9) Our results suggested that flavonoids and caffeoylquinic acid derivatives are the active XO inhibitory constituents in the flowers of C. sinense. Flavonoids and caffeoylquinic acid derivatives are groups of natural products with varied biological and pharmacological activities.…”
Section: Resultsmentioning
confidence: 88%
“…7) In a previous study, we reported that the methanolic extract of the flowers of this plant and its constituents showed potent inhibitory activity against XO in vitro. 8,9) The results suggested that flavonoids and caffeoylquinic acid derivatives may play an important role in the XO inhibitory activity of this plant. Therefore, in this study we investigated the in vivo hypouricemic effect of acacetin (1) and 4,5-O-dicaffeoylquinic acid methyl ester (2) (Fig.…”
mentioning
confidence: 94%
“…The main purpose of the present study was to determine the inhibitory effect of CYN on XOD activity since it is a target enzyme for the treatment of gout and related symptoms. [36], and the types of inhibition were determined as competitive. The competitive type of XOD inhibition with apigenin was also confirmed by Lin et al [34].…”
Section: Discussionmentioning
confidence: 99%
“…The isolation and structural analysis of the active compounds 13 and 14 clarified them to be luteolin and apigenin, respectively [13, . In previous studies, luteolin and apigenin was found to be XO inhibitors in the flowers and buds of Daphne genkwa (10), and the IC50 values for luteolin were reported to be between 0.6 and 11.6 mmol L 21 and between 0.36 and 0.7 mmol L 21 for apigenin (11)(12)(13)(14)(15). The IC50 value of the isolated luteolin and apigenin evaluated in this study were 2.3 and 3.0 mmol L…”
mentioning
confidence: 95%